2018
DOI: 10.7149/opa.51.4.51003
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Visualization of Nanopowder Combustion in Air

Abstract: The paper discusses the methods of high-speed imaging of high-temperature processes in a real time mode: passive registration in the own light, usage of laser illumination, and using the laser monitor. The visualization results of combustion in air of Al nanopowder and thermite Al-Fe2O3 mixture are presented. The perspectives of application of laser monitors in NDE are considered, particularly for the study of laser ignition of thermite mixtures and solid fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…The second scheme of high-speed imaging used in this work was the scheme with laser illumination. We used the scheme with laser illumination early with 532 nm wavelength and 5 mW power continuous DPSS laser in [11]. It was shown that the method of visualization with external laser illumination is good for panoramic view of the processes.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second scheme of high-speed imaging used in this work was the scheme with laser illumination. We used the scheme with laser illumination early with 532 nm wavelength and 5 mW power continuous DPSS laser in [11]. It was shown that the method of visualization with external laser illumination is good for panoramic view of the processes.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, aluminum-based materials obtained by high-temperature combustion of nanopowders in air offer a number of interesting and potentially high impact commercial opportunities [1][2][3][4][5][6][7][8][9]. Combustion of aluminum and iron nanopowders and their mixtures proceeds at temperatures above 2000 • C and is accompanied by a bright gloving and the scattering of combustion products in some cases [10,11]. Moreover, the combustion of nanopowders is a fast process with a flow rate of a few millimeters or centimeters per second.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations